An efficient reformulation of a multiscale method for the eddy current problem. Issue 5 (4th September 2017) - Schöbinger, Markus; Hollaus, Karl; Schöberl, Joachim
Abstract : Purpose: This paper aims to improve the efficiency of a numerical method to treat the eddy current problem on a laminated material, where using a mesh that resolves each individual laminate would be too computationally expensive. Design/methodology/approach: The domain is modeled using a coarse mesh that treats the laminated material as a bulk with averaged properties. The fine-structured behavior is recovered by introducing micro-shape functions in the ansatz space. One such method is analyzed to find further model restrictions. Findings: By using a special reformulation, it is possible to eliminate the additional degrees of freedom introduced by the multiscale ansatz at the cost of an additional modeling error that decreases with the laminate thickness. Originality/value: The paper gives a computationally more efficient approximate variant to a known multiscale method.